Triple-drug Therapy With Bevacizumab, Irinotecan, and Temozolomide Plus Tumor Treating Fields for Recurrent Glioblastoma: A Retrospective Study - Lu, Guangrong; Rao, Mayank; Zhu, Ping; Liang, Buqing; El-Nazer, Rasheda T.; Fonkem, Ekokobe; Bhattacharjee, Meenakshi B.; Zhu, Jay-Jiguang (Frontiers in Neurology, 2019)
Clinical studies treating pediatric and adult solid tumors such as glioblastoma (GBM) with a triple drug regimen of temozolomide (TMZ), bevacizumab (BEV), and irinotecan (IRI) [TBI] have demonstrated various efficacies, but with no unexpected toxicities. The TBI regimen has never been previously studied in recurrent GBM (rGBM) patients. In this retrospective study, we treated rGBM patients who had satisfactory bone marrow function with the TBI regimen. We identified 48 adult rGBM patients with a median age of 56 years (range: 26-76), who received Tumor Treating Fields (TTFields) treatment for 30 days or longer, and concurrent salvage chemotherapies. The patients were classified into two groups based on chemotherapies received: TBI (TBI+T, N=18) versus bevacizumab (BEV)-based chemotherapies (BBC+T, N=30). BBC regimens were either BEV monotherapy, BEV+IRI or BEV+CCNU. Patients in TBI+T group received on average 19 cycles of TMZ, 26 and 21 times infusions with BEV and IRI, respectively. Median overall survival (OS) and progression-free survival (PFS) for rGBM (OS-R and PFS-R) patients who received TBI+T were 18.9 and 10.7 months, respectively. In comparison, patients who received BBC+T treatment had OS-R and PFS-R of 11.8 (P>0.05) and 4.7 (P<0.05) months, respectively. Although the median PFS results were significantly different by 1.5 months (6.6 vs 5.1) between TBI+T and BBC+T groups, the median OS difference of 14.7 months (32.5 vs 17.8) was more pronounced, P<0.05. Patients tolerated TBI+T treatment well and there were no unexpected toxicities. The most common side effects from TBI+T treatment included grade III hypertension (38.9%) and leukopenia (22.2%). In conclusion, the TBI regimen might play a role in the improvement of PFS-R and OS-R among rGBM patients. Prospective studies with a larger sample size are warranted to study the efficacy and toxicity of TBI+T regimen for rGBM.